O.ÁBDIRAXMANOVTÍŃ SATIRALÍQ SHÍǴARMALARÍNÍŃ TEMATIKASÍ HÁM IDEYALÍQ BAǴDARLARÍ - Seytbekov, A.B. (SCIENCE and SOCIETY, 2024)
The article focuses on the study of the themes and ideological directions of satirical works in the works of O.Abdurakhmanov.